Ignorancia, retórica y revisión: las independencias en el discurso del nacionalismo historiográfico español - Antonio Sáez Arance (Caravelle)
The article deals with the role of historians of Spanish America for the shaping of a national historical discourse in 19th and 20th-Century Spain. It stresses the considerable continuity of a national-catholic interpretation of Spanish colonial past which reduces or even neglects the importance of the Spanish American Independence. Despite of the democratization process since 1975, apologetic approaches are still strong and influential in the public sphere. The way overcoming these tendencies should be a systematic de-nationalization and internationalization of Spanish historical research.